Macropterous species of genus Melanabropsis Wang & Liu, 2020 (Orthoptera: Anostostomatidae: Anabropsini) from the localities predicted in a previous study - Chen, Po-Wei (Zootaxa, 2024)
The genus Melanabropsis currently consists of four micropterous species and one macropterous species from continental Asia and west Pacific islands. Yin (2024) predicted several potential habitats suitable for Melanabropsis species including Taiwan and Guizhou. In this study two additional new species from Taiwan and Guizhou are described, confirming the distribution prediction proposed by Yin. The distribution pattern of seven Melanabropsis species is discussed.